Harry Potter and the prisoner of Azkaban - Rowling, J. K. (Thorndike, Me. : Thorndike Press, 1999)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.
2
Keywords: Large type books; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Schools -- Juvenile fiction; England -- Juvenile fiction